TINGKAT KEPUASAN NASABAH TERHADAP PRODUK DANA TABUNGAN SIMPATIK BANK SYARIAH MANDIRI KCP KAPUAS MELALUI KERJASAMA ANTARSEKOLAH - HARIS FAULIDI ASNAWI; SARKIAH SARKIAH (Islamic Economics and Business Faculty of UIN Antasari, 2014)
The main purpose of the customer to save money in the bank is for the future needs and the cost of education with ease and more secure transactions. This is consistent with the results of the Important Performance Analysis that show the important attributes while choose a Tabungan Simpatik product are security saving, responsive in serving every customers complaints, responsive serves for saving bookkeeping, administrative thoroughness, friendliness, and honesty of employees of Bank Syariah Mandiri KPC Branch Office Kapuas. Employees of Bank Syariah Mandiri KCP Kapuas also consider the interests of customers, and certainty of customer confidentiality.